2011
DOI: 10.1254/jphs.11031fp
|View full text |Cite
|
Sign up to set email alerts
|

Impairment by Hypoxia or Hypoxia/Reoxygenation of Nitric Oxide–Mediated Relaxation in Isolated Monkey Coronary Artery: the Role of Intracellular Superoxide

Abstract: Abstract.To investigate the effect of hypoxia or hypoxia/reoxygenation on vascular smooth muscle function, mechanical response of monkey coronary artery without endothelium was studied under normoxia, hypoxia, and hypoxia/reoxygenation. Hypoxia or hypoxia/reoxygenation impaired the relaxation by nitroglycerin or isosorbide dinitrate but not that by 8-bromoguanosine-3′,5′-cyclic monophosphate or isoproterenol. Tempol restored the impaired relaxation by nitroglycerin or isosorbide dinitrate, but superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…The impairment by hypoxia or by hypoxia/reoxygenation of BAY 41-2272-evoked relaxation in endothelium-denuded monkey coronary arteries observed in the present study was not so severe as that of NO donorsinduced relaxation observed in our previous study (9). Incidentally, this impairment of vasorelaxation in response to NO donors was also prevented by treatment with tempol (9), indicating that the crucial factor underlying the impairment is also superoxide.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The impairment by hypoxia or by hypoxia/reoxygenation of BAY 41-2272-evoked relaxation in endothelium-denuded monkey coronary arteries observed in the present study was not so severe as that of NO donorsinduced relaxation observed in our previous study (9). Incidentally, this impairment of vasorelaxation in response to NO donors was also prevented by treatment with tempol (9), indicating that the crucial factor underlying the impairment is also superoxide.…”
Section: Discussionsupporting
confidence: 63%
“…That is, these highly reactive species oxidize the sGC heme moiety from the ferrous (Fe 2+ ) to the ferric (Fe 3+ ) state and subsequently remove the heme from the enzyme, resulting in the increase in the ratio of the oxidized/heme-free form to the reduced form. In the previous study, we have shown that the tissue level of superoxide is increased by hypoxia or by hypoxia/reoxygenation in isolated endotheliumdenuded monkey coronary arteries (9). Consequently, the shift of sGC redox state under hypoxia or under hypoxia/reoxygenation observed in the present study was considered to be due to superoxide and/or its derivatives.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations